Si-29 and Al-27 MAS NMR spectra are affected by alkali metal cluster formation in zeolite LTA - Moran, K; Barker, P; Readman, J; Edwards, P; Dupree, R; Anderson, P (2000)
We report the application of 27Al and 29Si MAS NMR to provide a direct probe of alkali metal cluster formation and distribution in the α- cages of zeolite A (LTA).